Action research to explore the future language classroom with iPads - Gabarre, Cecile; Gabarre, Serge; Din, Rosseni; Yong, Mei Fung (2013)
In foreign language teaching and learning, technology mediated pedagogy fosters active participation by facilitating access to resources. However, current facilities such as computer laboratories and lecture classrooms often dictate how technology is to be accessed and thus limits the flexibility of course delivery. Ideally, classrooms should bridge the advantages of all settings and provide educators with mobile, versatile and reliable technology. Recent studies have shown that tablet computers can perform as interactive whiteboards, transform into mobile computer laboratories while catering for ubiquitous, individualised and collaborative learning. A qualitative action research was implemented to explore the ease-of-use and usefulness of introducing tablet computers from pedagogical and technological perspectives. The intervention was conducted in a French undergraduate course. The lecturer adapted and designed course material, selected applications and taught using the iPad. The data was collected through observations, artefacts and field notes, interviews, learners' self-reflexive logs as well as lecturers' memos before being analysed and coded using ATLAS.ti. Findings confirmed that the devices' features and applications were relevant to language teaching and learning. Embedded aids such as dictionaries and predictive text-input provided instant support. Multimedia recording and sharing tools engaged the learners in dynamic presentations. Additionally, an active online community provided useful resources for both learners and educators. Although designing and delivering course material necessitated some adaptation, the results outweighed the efforts. Nevertheless, the all-in-one technological and pedagogical advantages are hindered by connectivity issues. It is thus recommended to establish a conducive environment before iPads can be successfully incorporated in the classroom.